Fine-scale microhabitat selection in a bromeliad-dwelling jumping spider (Salticidae) - De Omena, Paula M.; Romero, Gustavo Q. [UNESP] (Wiley-Blackwell, 2008)
Although a wide variety of arthropods specialize on a specific host plant, little is known about the evolution of host-plant specialization in spiders. In several regions of South America, the Neotropical jumping spider Psecas chapoda associates with Bromelia balansae, a rosette-shaped plant that does not accumulate rain water in phytotelmata. We conducted experiments using bromeliad species with distinct architectures that were uncommon in the geographic range of R chapoda to investigate the level of spider specialization in microhabitat structure. We also tested the influence of phytotelmata and foliar spines on host plant selection. B. balansae, Ananas comosus and Aechmea distichantha (tank-bromeliad), which share similar traits (e.g. long and narrow leaves), were colonized in similar frequencies. Aechmea fasciata, a tank-bromeliad that has short and broad leaves, was never colonized by these spiders, and Aechmea blanchetiana, tank-bromeliad with long and broad leaves, was only colonized infrequently. The removal of foliar spines did not affect the number of R chapoda on B. balansae. Our findings suggest that microhabitat specialization by R chapoda is based on rosette and leaf architectures. This unusual specialization likely evolved because the bromeliads with such architecture (i.e. B. balansae) typically dominate the biogeographic area of R chapoda, and because this microhabitat provides specific benefits to spiders, as shelter, and as foraging and reproductive sites. (c) 2008 The Linnean Society of London.
Keywords: Bromeliaceae; Host plant selection; Plant architecture; specific associations